Consistency of the Initial and Updated Version of the Nutri-Score with Food-Based Dietary Guidelines: A French Perspective - Sarda, Barthelemy; Kesse-Guyot, Emmanuelle; Deschamps, Valérie; Ducrot, Pauline; Galan, Pilar; Hercberg, Serge; Deschasaux-Tanguy, Melanie; Srour, Bernard; Fezeu, Leopold K; Touvier, Mathilde; Julia, Chantal (The Journal of nutrition, 2024)
To help consumers to make healthier food choices, 7 European countries have implemented the front-of-pack nutrition label Nutri-Score. The algorithm was updated in 2022–2023 by the Nutri-Score European scientific committee, based on the current scientific knowledge. The aim of this study was to investigate the consistency of the newly internationally developed algorithm with the French food-based dietary guidelines (FBDG) and compare the respective performances of the initial and updated algorithm. Three complementary French food composition databases were used to access extensive coverage of the food supply in France (n = 46,752): the Oqali, OpenFoodFacts, and CIQUAL databases. Based on the French FBDG, a list of 41 criteria was defined by which the consistency between French FBDG and the Nutri-Score was assessed (eg, consumption of fresh vegetables is promoted in FBDG, thus the Nutri-Score should rate favorably such products). Of all criteria, the initial algorithm met 63% (26/41) of them, whereas the revised algorithm met 85% (35/41) of them. Improvements achieved by the updated version of the Nutri-Score in alignment with the FBDG were particularly observed for high-fat products (ie, fatty fish, nuts, and seeds), sweet products (ie, ice creams and sweet spreads), salty products (ie, savory snacks and salted nuts), dairy beverages, and beverages with artificial sweeteners. The Nutri-Score’s updated nutrient profiling system appears to rate foods more consistently regarding the French dietary guidelines and improved the currently existing system. This work supports the implementation of the updated nutrient profiling system underlying Nutri-Score.